2014
DOI: 10.1016/j.neuroscience.2014.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1 receptors in mouse pontine reticular formation modulate nociception only in the presence of systemic leptin

Abstract: Human obesity is associated with increased leptin levels and pain, but the specific brain regions and neurochemical mechanisms underlying this association remain poorly understood. This study used adult male C57BL/6J (B6, n = 14) mice and leptin-deficient, obese B6.Cg-Lepob/J (obese, n = 10) mice to evaluate the hypothesis that nociception is altered by systemic leptin levels and by adenosine A1 receptors in the pontine reticular formation. Nociception was quantified as paw withdrawal latency (PWL) in s after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…117,118 Further exploration has shown that some reticular formation receptors routinely involved in pain regulation do not work without leptin. 119 The administration of ibuprofen decreased glial activation with no effect on leptin expression in nucleus accumbens in the experimental setting. 117 These findings suggest that better understating of inflammation can create a platform for further developing the interchangeability of some drugs used for pain, behavioral disorders, and obesity.…”
Section: Metabolic and Inflammation Mechanismsmentioning
confidence: 97%
“…117,118 Further exploration has shown that some reticular formation receptors routinely involved in pain regulation do not work without leptin. 119 The administration of ibuprofen decreased glial activation with no effect on leptin expression in nucleus accumbens in the experimental setting. 117 These findings suggest that better understating of inflammation can create a platform for further developing the interchangeability of some drugs used for pain, behavioral disorders, and obesity.…”
Section: Metabolic and Inflammation Mechanismsmentioning
confidence: 97%
“…As noted previously [37] the relationship between leptin and obesity adds to the complexity of determining the degree to which leptin status and/or obesity alter nociception. The Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Given that leptin is produced by adipocytes, differentiating the extent to which nociception is modulated by leptin per se versus obesity is not trivial [37]. In an effort to evaluate the contributions of obesity and/or leptin to buprenorphine-induced antinociception, the present study used mice that share the obesity phenotype but differ in leptin signaling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations